Analisis Perilaku Belanja Online Mahasiswa Progam Studi Pendidikan IPS FKIP Universitas Tanjungpura - Ruhmini, Nor Lailatur; Karolina, Venny; Firmansyah, Haris; Kuswanti, Heni; Hafizi, M Zainul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to analyze online shopping behavior among students of the Social Sciences Education Study Program at Tanjungpura University. The approach used in this research is quantitative with a survey method using a questionnaire. This research involved respondents who were willing to fill out a questionnaire and had experience and understanding of online shopping. The data collected includes the frequency of online shopping that students do, the types of goods that students often buy, and the reasons why students do and do not shop online. The analysis was carried out using descriptive statistics to describe student shopping behavior patterns. The research results show that the majority of students shop online with a frequency of 3 or more times a month. Students tend to buy clothing products with 83.8% positive responses and cosmetics with 64.8% positive responses, with the main reason for shopping online being affordable prices with 93.7% positive responses and discounts with 88.3% positive responses. However, on the other hand, it turns out that there are still some students who have never done online shopping because they cannot see the goods clearly.